KOMPLEMEN DALAM KITAB YEHEZKIEL (SUATU ANALISIS SINTAKSIS) - PAAT, SHASMITA FRIDA YURIKE (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2016)
ABSTRACT This research is entitled Complements in the Book of Ezekiel (a syntactical analysis). It used the New International Version (NIV). This research has two statement of problems: (1) what kind of complements in the Book of Ezekiel? and (2) what are their position in the sentences in the Book of Ezekiel? The method used in this research is descriptive method, which is divided into three steps. First is preparation, the writer read the Book of Ezekiel and some books that related to this title. Second is data collection, the writer collect the data, identify and classify the complement. Third is data analysis, the writer determine the subject, predicate, the kinds and position of complement. This research used Forlini and friends’ (1987) theory. They said that complement is a word or group of words that completes the meaning of the predicate of a sentence and distribute it in five different kinds, they are Direct Object, Indirect Object, Objective Complement, Predicate Nominative, and Predicate Adjective. There are 48 chapters in the book of Ezekiel, but this research just selected 24 chapters from chapter 1-24. The 494 sentences in the 24 chapters have complements. The conclution of this research shows that: (1) all of the kind of complements are found. (2) The position of Direct Object are after predicate; after indirect object; before objective complement; with predicate nominative; with predicate adjective; with indirect object and objective complement; and with indirect object and predicate nominative. The position of Indirect Object are between predicate and direct object; with objective complement; and with predicate nominative. The position of Objective Complement are after direct object; and with indirect object. The position of Predicate Nominative are after the linking verb; with direct object; with indirect object; and with predicate adjective. The position of Predicate Adjective are after linking verb; with direct object; with indirect object; and with predicate nominative. Keywords: complement, adjective complement, predicate nominative.